Taxation and Economic Growth in Nigeria - Babatunde, ONAKOYA Adegbemi; Ibukun, AFINTINNI Oluwatobi (Asian Journal of Economic Modelling, 2016)
Over several decades, taxation has been taken as a veritable medium of engineering the growth or performance of an economy. However, empirical literature is not conclusive, as several studies have indicated mixed effects of tax on economic growth. Arising from this, the study investigated the cointegration relationship between tax revenue and Economic growth in Nigeria from 1980 to 2013. Various preliminary tests including descriptive statistics, trend analysis, and stationary tests using Augmented Dickey Fuller (ADF) test were conducted. The Engle-Granger Cointegration test was employed to determine whether a long run relationship existed between the variables. The Vector Error correction model was employed to confirm the long run relationship and determine the short run dynamics between the variables. Two post estimation diagnostics tests (autocorrelation, and Heteroscedasticity) were also conducted in order to confirm the robustness of the model. Findings indicated that a long run (but no short run) relationship existed between taxation and economic growth in Nigeria. The result also, revealed a significant positive relationship at 5% level of significance between Petroleum profit tax, Company Income tax and economic growth, but a negative relationship between economic growth and customs and Excise Duties. However, the tax components are jointly insignificant in impacting the Nigerian economic growth. This study recommends strong institutional reforms in the Department of Customs in order to plug the manifest leakages. The tax collection mechanism used by tax officials must be free from corruption and embezzlement. If this is not done, the revenue collected many not reach the desired point. The Federal Government, state governments and local governments should urgently modernize and automate all its tax system.